PENERAPAN ACTIVITY BASED MANAGEMENT UNTUK MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA PT. MODEREN PLASINDO MUTIARA PLASTIK - Samosir, Guido Giovani; Silalahi, Evelin Roma Riauli (Jurnal Ilmiah Akuntansi (JIMAT), 2022)
This study aims to determine the application of Activity Based Management in increasing the efficiency of production costs at PT. Modern Plasindo Mutiara Plastik. The population in this study is Production Costs, Non-Production Costs, and Production Activity Data in 2020. The samples used in this study are Production Costs, Non-Production Costs, and Production Activity Data for 2020. The data analysis technique used is descriptive analysis. Based on the results of the analysis and evaluation, it can be concluded that the realization of production costs for each element of production costs using the Traditional method of cost realization is Rp. 179,847,642,267. Meanwhile, the realization of production costs using the Activity Based Management method is Rp. 178,339,161,857. Based on the comparison of the two methods, it can be seen that the difference in costs is Rp. 1,508,480,410. It can be seen that the implementation of Activity Based management can identify value-added activities and non-value-added activities. So the level of production cost efficiency by using the Activity Based Management method the company can save costs up to 2%. Therefore, companies need to apply the Activity Based Management method to eliminate these value-added activities so that production cost efficiency will be achieved. Keywords: Activity Based Management, Production Cost Efficiency, Value Added Activities, Non Value Added